New cardiovascular prevention guidelines: How to optimally manage dyslipidaemia and cardiovascular risk in 2021 in patients needing secondary prevention? - Atar, Dan; Jukema, J. Wouter; Molemans, Bart; Taub, Pam R.; Goto, Shinya; Mach, François; CerezoOlmos, Cesar; Underberg, James; Keech, Anthony; Tokgözoğlu, Lale; Bonaca, Marc P. (Atherosclerosis, 2021)
Elevated low-density lipoprotein cholesterol (LDL-C) is a principally modifiable cause of atherosclerotic cardiovascular disease; accordingly, recent European and US multisociety dyslipidaemia guidelines emphasise the importance of lowering LDL-C to reduce cardiovascular risk. This review provides perspectives on established and emerging agents that reduce LDL-C to help providers synthesize the abundance of new evidence related to prevention of cardiovascular disease. We provide hypothetical cases of patients with different cardiovascular risk factors and medical histories to illustrate application of current lipid-lowering guidelines in various clinical settings. As a core focus of preventive therapy, both European and US lipid management guidelines emphasise the importance of identifying patients at very high cardiovascular risk and treating to achieve LDL-C levels as low as possible, with European guidelines setting a goal of <1.4 mmol/L (<55 mg/dL) in patients with very high-risk cardiovascular disease. The proprotein convertase subtilisin/kexin type 9 inhibitors are now included in the guidelines and may fulfil an important unmet need for very high-risk patients who are not able to achieve LDL-C goals with conventional agents. The recently approved bempedoic acid and other promising agents under development will add to the armamentarium of lipid-lowering drugs available for clinicians to help patients meet their treatment goals. [Display omitted] •New guidelines emphasise more intensive LDL-C lowering depending on cardiovascular risk.•The revised guidelines now provide a well-defined role for PCSK9 inhibitors.•Emerging therapies, including bempedoic acid, may soon impact the treatment landscape.•We address non–LDL-C therapies with outcomes data in high risk populations.•We provide case studies focussing on application of guidelines in very high-risk patients.